PENGARUH IKLIM ORGANISASI DAN MOTIVASI MENGAJAR TERHADAP KINERJA PROFESIONAL GURU SMA, SMK, MA MUHAMMADIYAH DI KABUPATEN KUDUS (QUALITY, 2016)
This research aims to know the organizational climate influence and teaching motivation towards the teachers’ professional performance of SMA, SMK and MA Muhammadiyah in Kudus year 2015/2016. The population in this study was the teachers of SMA, SMK and MA Muhammadiyah in Kudus 2015. The number of the population is 257 teachers with research sample of 156 teachers. The data collected by using question form. Data analyzed with regression analysis. The results showed that: (1) based on the respondents’ perception toward the organizational climate, were obtained value ranges 116-150, with a total score of 20 409 and an average score of 130.79 which in this case includes a good enough category. (2) based on the respondents perceptions about the workforce teaching motivation influence gained from the score of teacher performance range 107-151, with a total score of 20,191.00 and an average score of 134.43 was a good category either. (3) based on the level of influence the organization's climate variables (X 1) and a variable motivational teaching (X 2) against the performance of teachers (Y) amounted to 0.73 or 73.0%. This number shows that performance of the teacher (Y) simultaneously (simultaneous) influenced by the organization's climate variables (X1) and motivational teaching variable (X2) of 73.0% while the remaining 27% were influenced by other factors.